Uptake of second-line anticancer therapy after first-line pembrolizumab in patients with stage IV non–small cell lung cancer with PD-L1 > 50%: Comparison between clinical trials and the real world. Issue 28 (1st October 2022) - Rittberg, Rebekah; Jones, Lauren; Leung, Bonnie; Shokoohi, Aria; Ionescu, D N; Pender, Alexandra; Yuan, Ren; Wong, Selina K.; Al-Hashami, Zamzam Salam; Wang, Ying; Ho, Cheryl
Abstract : 126 Background: In KEYNOTE-024 single agent pembrolizumab was compared to platinum-based chemotherapy in advanced non-small cell lung cancer (NSCLC) with PDL1 >50%. Patients treated with pembrolizumab had an improved progression free survival and overall survival (OS). In KEYNOTE-024, 53% of patients treated with pembrolizumab received second line anticancer therapy with a median OS of 26.3 months. The objective of this study is to characterize real-world NSCLC patients who received second line therapy after pembrolizumab. Methods: A retrospective study of stage IV NSCLC patients with PDL1 >50% referred to BC Cancer between 2018-2021 treated with first line pembrolizumab. Patient demographics, treatment received, and outcomes were collected retrospectively. Baseline characteristics were compared using descriptive statistics. Univariate and multivariate analysis was completed. Kaplan-Meier curves was used to calculate OS and compared using the log rank test. Results: Between 2018-2021, 718 Stage IV NSCLC patients received at least 1 cycle of pembrolizumab. Median duration on treatment was 4.4 months and follow up duration was 16.0 months. 567 (80%) had disease progression of which only 21% (n = 119) received second line systemic therapy. Within the subset with disease progression, median duration on treatment was 3.0 months and follow up duration was 11.7 months. Patients who received second line therapy were younger (p < 0.001), better baseline ECOG PS (p < 0.001) and had longer duration on first line pembrolizumab (p < 0.001). There was no difference in sex (p = 0.519), smoking status (p = 0.416) or histology (p = 0.136). In the multivariate model including age (OR 0.95), baseline ECOG PS (PS 0-1, OR 2.59) and duration on pembrolizumab (OR 1.05) each independently impacted receipt of second line therapy, Table. Median OS from date of diagnosis was 9.6 (IQR 8.4-10.9) months in patients who did not receive additional therapy after progression and 25.3 (IQR 22.5-28.1) months in patients who received subsequent therapy, (p < 0.001). Conclusions: In our stage IV NSCLC population, we found that only 21% of patients received second line systemic therapy despite it being associated with improved OS. Compared to KEYNOTE-024, this real-world population found that 60% less patients received second line systemic therapy. Although differences exist between a clinical and non-clinical trial population, these findings suggest significantly undertreating our stage IV NSCLC patients requiring increased rates of offering second line therapy.Multivariable analysis for characteristics associated with receipt of second line systemic therapy. OR (95% CI) Multivariate analysis P-Value Age 0.949 (0.927-0.972) < 0.001 ECOG PS 0-1 versus = / >2 2.591 (1.610-4.167) < 0.001 Duration of Pembrolizumab 1.053 (1.023-1.085) < 0.001